Developing a new neutral DEA model for media selection in the existence of imprecise data. (1st January 2013) - Azadi, Majid; Saen, Reza Farzipoor; Momeni, Ehsan
An appropriate advertising media selection has a strategic significance for every firm. Media selection problem is an important yet complex decision which requires careful consideration of multiple criteria. One of the techniques that can be used for selecting the media is data envelopment analysis (DEA). Neutral data envelopment analysis (NDEA) model is one of the new models in data envelopment analysis (DEA). In many real world applications, data are often imprecise. A successful approach to address uncertainty in data is to replace crisp data via imprecise data, leading to imprecise DEA (IDEA). In this paper, an imprecise NDEA (INDEA) model is developed for media selection. Finally, a numerical example demonstrates the application of the proposed model.